Molybdenum-doped carbon-nitrogen photocatalytic material as well as preparation method and application thereof

By doping molybdenum into the carbon nitride photocatalyst, C3N5/Mo materials with high specific surface area and excellent photocatalytic performance were prepared, which solved the problem of low degradation efficiency of existing carbon nitride photocatalysts in wastewater treatment and achieved efficient degradation of various organic matter.

CN119771474AActive Publication Date: 2025-04-08SHANXI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510147343.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-08
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing carbon nitride photocatalysts have problems of carrier recombination and low specific surface area during photocatalytic degradation, which limits their application in wastewater treatment.

Method used

The molybdenum-doped carbon-nitrogen photocatalytic material (C3N5/Mo) was prepared by reaction with molybdate by the "one-pot method" condensation polymerization, which improved the specific surface area and photocatalytic properties of the material.

Benefits of technology

This material has extremely strong degradation ability to organic matter such as methyl orange, methylene blue, rhodamine, olerachin, etc. under visible light, which significantly improves the efficiency of sewage treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771474A_ABST
    Figure CN119771474A_ABST
Patent Text Reader

Abstract

The invention provides a molybdenum-doped carbon-nitrogen photocatalytic material as well as a preparation method and application thereof. The preparation method comprises the following steps: grinding 3-amino-1, 2, 4-triazole and molybdate in a mortar, and pouring into a crucible; then putting the mixture into a muffle furnace, reacting for 2-3 hours at the temperature of 500-560 DEG C, and naturally cooling to obtain a light earthy yellow powdery material C3N5 / Mo. The material has relatively low recombination rate of light generation e <-> and h < + >, and has extremely strong degradation capability on organic matters such as methyl orange, methylene blue, rhodamine and oxytetracycline under visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photocatalytic material, in particular to a molybdenum-doped carbon-nitrogen photocatalytic material and a preparation method and application thereof. Background Art

[0002] The photocatalytic properties of graphite carbon nitride (CN) are attracting more and more attention. Since the redox reaction caused by the photoinduced generation of holes and electrons can photodegrade pollutants, carbon nitride is expected to be used in wastewater treatment. In the early stage, people used melamine to synthesize C3N4. Due to its wide band gap and narrow absorption range (λ<450nm), its application was limited. Later, scientists discovered that C3N 5。 As a new type of carbon nitride photocatalyst, C3N5 has high nitrogen content and narrow band gap, and shows extraordinary performance in the field of photocatalysis. However, C3N5 also has inherent disadvantages such as carrier recombination and low specific surface area.

[0003] Doping strategy is a relatively direct and effective method to improve photocatalytic activity. It can directly affect the band structure by introducing intermediate energy levels or narrowing the band gap, thereby enhancing visible light absorption and changing the redox potential. The empty intermediate band can accommodate photoexcited electrons from the valence band, which helps to absorb photons with energy below the band gap. Noble metals, such as Au, Pt, and Pd, have been widely used as effective doping materials. However, the high cost of noble metals limits their practical application. From a practical point of view, it is imperative to develop resource-rich, low-cost, non-noble metal doping materials to improve photocatalytic performance. Summary of the invention

[0004] The main purpose of the present invention is to provide a molybdenum-doped carbon-nitrogen material (abbreviated as C3N5 / Mo material) and its preparation method and application. 3-amino-1,2,4-triazole is used as the synthetic raw material of C3N5, molybdate is doped in the reaction process, and the target product C3N5 / Mo is synthesized by a "one-pot method" condensation polymerization. The synthesis yield is high and the repeatability is strong. The material has a low photogenerated e - and h + The photocatalytic reaction is highly effective in degrading organic matter such as methyl orange, methylene blue, rhodamine and oxytetracycline under visible light. The invention aims to solve the problem of organic matter being difficult to degrade in sewage treatment plants by using photocatalytic technology.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A molybdenum-doped carbon-nitrogen photocatalytic material, wherein the photocatalytic material is a C3N5 / Mo material.

[0007] Preferably, the photocatalytic material has a band gap of 1.87 eV; the microstructure morphology is irregular granular; the X-ray powder diffraction data are 13.133, 16.129, 18.830, 23.540, 27.184, 29.117, 45.916 and 57.320 degrees; the infrared spectrum data are 495, 804, 1204, 1240, 1321, 1403, 1458, 1546, 1635, 3085 cm -1 .

[0008] The present invention also discloses a method for preparing the above-mentioned molybdenum-doped carbon-nitrogen photocatalytic material, comprising the following steps:

[0009] 1) Grinding 3-amino-1,2,4-triazole and molybdate in a mortar at a molar ratio of 500:1 to 600:1, and then pouring the mixture into a crucible;

[0010] 2) placing the crucible in a muffle furnace and heating it to 500-560° C. to react for 2-3 hours to obtain the molybdenum-doped carbon-nitrogen photocatalytic material.

[0011] The microscopic morphology of the catalyst prepared by the present invention is mainly irregular small particles, the size of the particles is smaller, and the particles are distributed more evenly after grinding, which greatly increases the specific surface area of ​​the catalyst.

[0012] The present invention uses 3-amino-1,2,4-triazole as a raw material because it is rich in nitrogen, which makes it an ideal raw material for preparing C3N5, a high-nitrogen content material. From a structural point of view, the distribution of nitrogen atoms in its molecular structure is conducive to building the structural skeleton of C3N5 through appropriate reactions. In the reaction process, it can provide a nitrogen source for the generation of C3N5 and contribute to the generation of its specific structure through atomic rearrangement, breaking and forming chemical bonds, etc.

[0013] Furthermore, the molybdate described in step 1) is sodium molybdate, potassium molybdate or amine molybdate.

[0014] Furthermore, the molar ratio of 3-amino-1,2,4-triazole to molybdate in step 1) is 575:1.

[0015] Furthermore, the particle size of the sample after grinding in step 1) is mainly distributed between 0.1 and 15 microns.

[0016] Furthermore, in step 2), the reaction temperature is 550° C. and the reaction time is 3 hours.

[0017] Furthermore, the heating rate of step 2) is in the range of 3 to 6° C. per minute.

[0018] The present invention also provides the use of the photocatalytic material in photocatalytic degradation of organic pollutants.

[0019] Furthermore, the organic pollutant is a mixture of one or more of methyl orange, methylene blue, rhodamine, oxytetracycline and penicillin.

[0020] It can be seen from the above technical solutions that compared with the prior art, the present invention has the following excellent effects:

[0021] Due to the doping of metallic molybdenum, the oxygen vacancies in the C3N5 structure increase, and the photogenerated electrons are transferred to molybdenum, resulting in the material having a lower photogenerated electron density. - and h + Compared with some existing photocatalytic materials, C3N5 / Mo material has a strong ability to degrade organic substances such as methyl orange, methylene blue, rhodamine, oxytetracycline and penicillin under visible light, and has obvious performance advantages. This invention is expected to solve the problem of wastewater degradation discharged by sewage treatment plants, pharmaceutical companies, hospitals, large slaughterhouses, dyeing workshops and other enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0023] Figure 1 This is the X-ray powder diffraction pattern of the photocatalytic material prepared in Example 1 of the present invention.

[0024] Figure 2 This is the infrared spectrum of the photocatalytic material prepared in Example 1 of the present invention.

[0025] Figure 3 This is the ultraviolet diffuse reflection image of the photocatalytic material prepared in Example 1 of the present invention.

[0026] Figure 4 This is a particle size distribution diagram of the photocatalytic material prepared in Example 1 of the present invention.

[0027] Figure 5 This is a photograph of the photocatalytic material prepared in Example 1 of the present invention.

[0028] Figure 6 This is a microscopic morphology of the photocatalytic material prepared in Example 1 of the present invention.

[0029] Figure 7 This is a graph showing the degradation of methyl orange by the photocatalytic materials prepared in Example 1 of the present invention and Comparative Example 1.

[0030] Figure 8 This is a graph showing the degradation of methylene blue by the photocatalytic materials prepared in Example 1 of the present invention and Comparative Example 1.

[0031] Fig. 9 This is a graph showing the degradation of rhodamine by the photocatalytic materials prepared in Example 1 of the present invention and Comparative Example 1.

[0032] Fig.10 This is a graph showing the degradation of oxytetracycline by the photocatalytic materials prepared in Example 1 of the present invention and Comparative Example 1.

[0033] Fig.11 This is a graph showing the degradation of penicillin by the photocatalytic materials prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] Weigh 2 grams of 3-amino-1,2,4-triazole and 0.010 grams of sodium molybdate dihydrate into a mortar and grind for three minutes, then pour into a 30 ml crucible. Then put it into a muffle furnace, raise it to 550°C within 100 minutes, keep it at 550°C for 3 hours, and cool it naturally to obtain a light khaki powder, which is recorded as C3N5 / Mo-1, with a yield of 40%.

[0037] The X-ray powder diffraction results are as follows Figure 1 .Depend on Figure 1 It can be seen that the peaks at 13.133 and 27.184 are the characteristic peaks of C3N5; the peaks at 16.129, 18.830, 23.540, 29.117, 45.916 and 57.320 are the characteristic peaks of the molybdate used, which fully demonstrates the successful preparation of the sample.

[0038] Figure 2 This is the infrared spectrum of the sample. -1 The peak at 804cm is caused by the symmetrical or asymmetrical vibration of Mo-O-Mo; -1 The peaks at 1635, 1546, 1458, 1403, 1321, 1240, 1204 cm-1 are caused by the CN bending vibration in the triazine unit; -1 It is caused by CN and C=N stretching vibration; 3085cm -1The peak at is caused by the NH stretching vibration of the uncondensed amino group.

[0039] Figure 3 This is the UV diffuse reflectance image of the prepared sample. It can be seen that the band gap of the material is 1.87eV.

[0040] Figure 4 The particle size distribution diagram of the prepared sample after grinding is shown in Figure 1. It can be seen that the particle size of the sample after grinding is mainly distributed between 0.1-15 microns, and 70% of the particle size is below 5 microns.

[0041] Figure 5 This is a photo of the photocatalytic material prepared in Example 1 of the present invention.

[0042] Figure 6 This is a scan of the microscopic morphology of the prepared sample. It can be seen that after a period of sintering, some small spherical particles are dispersed on the surface of the sample, which helps to increase the specific surface area of ​​the sample and thus improve the catalytic efficiency.

[0043] Example 2

[0044] Weigh 2 grams of 3-amino-1,2,4-triazole and 0.005 grams of sodium molybdate dihydrate into a mortar and grind for three minutes, then pour into a 30 ml crucible. Then put it into a muffle furnace, raise it to 550°C within 180 minutes, and keep it at 550°C for 3 hours, cool it naturally, and obtain a yellowish brown powder, which is recorded as C3N5 / Mo-2, with a yield of 60%.

[0045] Comparative Example 1

[0046] Preparation of pure C3N5: Weigh 2 g of 3-amino-1,2,4-triazole and grind it in a mortar for three minutes, then pour it into a 30 ml crucible. Then put it into a muffle furnace, heat it to 550°C within 180 minutes, and keep it at 550°C for 3 hours, cool it naturally, and obtain a brown-yellow powder, which is recorded as C3N5, with a yield of 60%.

[0047] Example 3

[0048] Photodegradation experiment of methyl orange: 5 mg of the photocatalyst powder prepared in Example 1 and Comparative Example 1 were respectively dispersed into 50 ml of methyl orange solution (10 mg / L). The visible light source was a 300w xenon lamp, 15 cm away from the liquid surface. The solution was ultrasonicated for 0.5 hours and kept in the dark for 0.5 hours to reach the adsorption-desorption equilibrium of methyl orange. The solution was continuously stirred under magnetic stirring to maintain a suspended state. A condensation pump was used to maintain the reaction temperature at 20°C. The reaction was continued for 30 minutes, 1 ml of sample was taken every 5 minutes, and the catalyst in the solution was removed by centrifugation. The absorbance was recorded using a Varian 50Bio UV-visible spectrophotometer. The results are as follows: Figure 7 .Depend on Figure 7It can be seen that after 20 minutes of turning on the light, compared with the pure C3N5 group, the degradation effect of the catalyst on methyl orange can reach about 75% after adding metal Mo, while the pure C3N5 group is only about 20%. After turning on the light for 60 minutes, the degradation efficiency of C3N5 doped with metal Mo can reach about 90%, while the pure C3N5 group is only about 40%.

[0049] Example 4

[0050] Photodegradation experiment of methylene blue: 5 mg of the photocatalyst powder prepared in Example 1 and Comparative Example 1 were dispersed into 50 ml of methylene blue solution (10 mg / L) respectively. The visible light source was a 300w xenon lamp, 15 cm away from the liquid surface. The solution was ultrasonicated for 0.5 hours and kept in the dark for 0.5 hours to reach the adsorption-desorption equilibrium of methylene blue. The solution needs to be stirred continuously under magnetic stirring to maintain a suspended state. The reaction temperature was maintained at 20°C using a condensation pump. The reaction was continued for 30 minutes, 1 ml of sample was taken every 5 minutes, and the catalyst in the solution was removed by centrifugation. The absorbance was recorded using a Varian50 Bio UV-visible spectrophotometer. The results are as follows: Figure 8 .Depend on Figure 8 It can be seen that 20 minutes after the light was turned on, compared with the pure C3N5 group, the degradation effect of the catalyst on methylene blue after the addition of metal Mo can reach about 91%, while the degradation efficiency of the pure C3N5 group is only 70%. After 30 minutes of turning on the light, the degradation efficiency of the catalyst added with metal Mo can reach 99%.

[0051] Example 5

[0052] Photodegradation of methylene blue experiment: 5 mg of the photocatalyst powder prepared in Example 1 and Comparative Example 1 were dispersed into 50 ml of rhodamine solution (10 mg / L) respectively. The visible light source was a 300w xenon lamp, 15 cm away from the liquid surface. The solution was ultrasonicated for 0.5 hours and kept in the dark for 0.5 hours to reach the adsorption-desorption equilibrium of methylene blue. The solution needs to be stirred continuously under magnetic stirring to maintain a suspended state. The reaction temperature was maintained at 20°C using a condensation pump. The reaction was continued for 30 minutes, 1 ml of sample was taken every 5 minutes, and the catalyst in the solution was removed by centrifugation. The absorbance was recorded using a Varian50 Bio UV-visible spectrophotometer. The results are as follows: Fig. 9 .Depend on Fig. 9 It can be seen that after 30 minutes of darkness, the catalyst reached adsorption equilibrium. After 20 minutes of light on, compared with the pure C3N5 group, after the addition of metal Mo, the degradation effect of the catalyst on rhodamine can reach about 95%, which is about 4.75 times that of the pure C3N5 group.

[0053] Example 6

[0054] Photodegradation of oxytetracycline experiment: 5 mg of the photocatalyst powder prepared in Example 1 and Comparative Example 1 were dispersed into 50 ml of oxytetracycline solution (10 mg / L) respectively. The visible light source was a 300w xenon lamp, 15 cm away from the liquid surface. The solution was ultrasonicated for 0.5 hours and kept in the dark for 0.5 hours to reach the adsorption-desorption equilibrium of methylene blue. The solution needs to be stirred continuously under magnetic stirring to maintain a suspended state. The reaction temperature was maintained at 20°C using a condensation pump. The reaction was continued for 30 minutes, 1 ml of sample was taken every 5 minutes, and the catalyst in the solution was removed by centrifugation. The absorbance was recorded using a Varian50 Bio UV-visible spectrophotometer. The results are as follows: Fig.10 .Depend on Fig.10 It can be seen that after 30 minutes of darkness, the catalyst reaches adsorption equilibrium. After 30 minutes of light on, the degradation effect of oxytetracycline in the C3N5 group samples is not ideal, but after adding metal Mo, about 60% of oxytetracycline can be degraded.

[0055] Example 7

[0056] Photodegradation of penicillin experiment: 5 mg of the photocatalyst powder prepared in Example 1 and Comparative Example 1 were dispersed into 50 ml of penicillin solution (10 mg / L) respectively. The visible light source was a 300w xenon lamp, 15 cm away from the liquid surface. The solution was ultrasonicated for 0.5 hours and kept in the dark for 0.5 hours to reach the adsorption-desorption equilibrium of methylene blue. The solution needs to be stirred continuously under magnetic stirring to maintain a suspended state. A condensation pump was used to maintain the reaction temperature at 20°C. The reaction was continued for 30 minutes, 1 ml of sample was taken every 5 minutes, and the catalyst in the solution was removed by centrifugation. The absorbance was recorded using a Varian50 Bio UV-visible spectrophotometer. The results are as follows: Fig.11 .Depend on Fig.11 It can be seen that after 30 minutes of darkness, the catalyst reaches adsorption equilibrium. After 30 minutes of light on, the degradation effect of C3N5 group samples on penicillin is not ideal, only about 20%. After adding metal Mo, the degradation efficiency can reach 65%.

[0057] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A molybdenum-doped carbon-nitrogen photocatalytic material, characterized in that: The photocatalytic material is C3N5 / Mo material.

2. The molybdenum-doped carbon-nitrogen photocatalytic material according to claim 1, characterized in that: The photocatalytic material has a band gap of 1.87 eV; the microstructure morphology is irregular granular; the X-ray powder diffraction data are 13.133, 16.129, 18.830, 23.540, 27.184, 29.117, 45.916 and 57.320 degrees; the infrared spectrum data are 495, 804, 1204, 1240, 1321, 1403, 1458, 1546, 1635, 3085 cm -1 .

3. The method for preparing a molybdenum-doped carbon-nitrogen photocatalytic material according to claim 1 or 2, characterized in that: The steps include: 1) Grinding 3-amino-1,2,4-triazole and molybdate in a mortar at a molar ratio of 500:1 to 600:1, and then pouring the mixture into a crucible; 2) placing the crucible in a muffle furnace and heating it to 500-560° C. to react for 2-3 hours to obtain the molybdenum-doped carbon-nitrogen photocatalytic material.

4. The molybdenum-doped carbon-nitrogen photocatalytic material according to claim 3, characterized in that: The molybdate described in step 1) is sodium molybdate, potassium molybdate or amine molybdate.

5. The molybdenum-doped carbon-nitrogen photocatalytic material according to claim 3, characterized in that: The particle size of the material after grinding in step 1) ranges from 1 to 15 microns.

6. The molybdenum-doped carbon-nitrogen photocatalytic material according to claim 3, characterized in that: The molar ratio of 3-amino-1,2,4-triazole to molybdate in step 1) is 575:

1.

7. The molybdenum-doped carbon-nitrogen photocatalytic material according to claim 3, characterized in that: Step 2) The reaction temperature is 550°C and the reaction time is 3 hours.

8. The molybdenum-doped carbon-nitrogen photocatalytic material according to claim 3, characterized in that: Step 2) The heating rate range is 3 to 6°C per minute.

9. Use of the photocatalytic material prepared by the preparation method according to any one of claims 3 to 8 in photocatalytic degradation of organic pollutants.

10. The use according to claim 9, characterized in that: The organic pollutant is a mixture of one or more of methyl orange, methylene blue, rhodamine, oxytetracycline and penicillin.

Citation Information

Patent Citations

  • Carbon dot-molybdenum trioxide and carbon nitride composite catalyst, preparation method and applications thereof

    CN107803215A

  • Mo doped graphite phase carbon nitride nanosheet powder and preparation method thereof

    CN108273540A

  • Molybdenum-doped graphite-phase carbon nitride catalyst as well as preparation method and application thereof

    CN110302824A

  • Molybdenum trioxide in-situ intercalation carbon nitride composite catalyst and preparation method thereof

    CN113751048A

  • Yb doped g-C3N5 composite photocatalytic material as well as preparation method and application thereof

    CN113893845A